ANALISIS KRITIS RELEVANSI TEOLOGIS PERJANJIAN LAMA BAGI SPIRITUALITAS INJILI DALAM KONTEKS WACANA POST-TRUTH - Jeane Paathh; Dicky Welly Kansil (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2025)
This study examines the theological contribution of the Old Testament to the formation of Evangelical spirituality within the context of the post-truth era, which is characterized by moral relativism, a crisis of authority, and a shifting understanding of truth. The purpose of this research is to identify the Old Testament spiritual values relevant to the renewal of contemporary Evangelical spirituality, such as the fear of God, steadfast love, obedience to the Word, and social justice. The research employs a qualitative method with a biblical-theological approach and literature analysis, exploring Old Testament texts and contemporary theological perspectives. The findings indicate that Evangelical spirituality rooted in Old Testament principles can strengthen faith, shape spiritual character, and provide a relevant theological response to the challenges of the post-truth era. The discussion emphasizes the importance of recontextualizing these theological values for today’s church in developing spirituality that is both contextual and God-centered.